2019
DOI: 10.2147/ijn.s191267
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effects of triptolide and methotrexate nanosuspensions on left ventricular remodeling in autoimmune myocarditis rats</p>

Abstract: PurposeThis study was carried out to investigate the effects of a triptolide (TP) nanosuspension and methotrexate (MTX) nanosuspension on left ventricular remodeling and cardiac function for autoimmune myocarditis (EAM) in rats. The regulating effects on inflammatory cytokines in the peripheral serum and related mechanisms are also discussed.MethodsFirst, TP and MTX were prepared as a nanosuspension, and the EAM model was successfully established in rats with cardiac myosin. Then, the effect of TP and MTX susp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
0
6
1
1
Order By: Relevance
“…Notably, triptolide combined with Western drugs, such as methotrexate, has previously been reported to produce favorable results in past experiments [35]. However, the number of predicted combinations containing triptolide in our model was not high; it predicted triptolide combined with diclofenac (75 times), naproxen (75 times), and celecoxib (24 times) but did not predict triptolide combined with methotrexate (0 times).…”
Section: Discussioncontrasting
confidence: 55%
“…Notably, triptolide combined with Western drugs, such as methotrexate, has previously been reported to produce favorable results in past experiments [35]. However, the number of predicted combinations containing triptolide in our model was not high; it predicted triptolide combined with diclofenac (75 times), naproxen (75 times), and celecoxib (24 times) but did not predict triptolide combined with methotrexate (0 times).…”
Section: Discussioncontrasting
confidence: 55%
“…Li et al. ( 2019 ) conducted experiments in a rat model of autoimmune myocarditis, and found that excessive collagen deposition and type I/III collagen ratio increased significantly, the left ventricular diastolic function was impaired, accompanied by increased cardiac volume and weakened elasticity and contractility function. Although moderate collagen production is a repair process under certain conditions, once the balance between collagen synthesis and degradation is broken, it results in the deposition of ECM and further deposition of collagen fibres in the interstitial and perivascular areas (Lv et al.…”
Section: Discussionmentioning
confidence: 99%
“…TPL has limited effects due to its poor solubility, toxicity and water solubility, while a newly developed water-soluble minnelide, has been recently reported to show promising activity in malignancies [ 36 - 40 ]. However, the clinical effect on myocardial fibrosis has not been reported at present, and the relevant studies are all carried out with TPL [ 11 , 17 , 41 - 43 ]. Considering that the focus of this study was to explore the mechanism of whether TPL could improve the degree of MF in MF rats by inhibiting the NF-κB pathway and the activation of NLRP3 inflammasome.…”
Section: Discussionmentioning
confidence: 99%